2010
DOI: 10.1002/prep.201000080
|View full text |Cite|
|
Sign up to set email alerts
|

Highly Insensitive/Reactive Thermite Prepared from Cr2O3 Nanoparticles

Abstract: Thermites prepared from nanoparticles are currently the subject of growing interest due to their increased performances compared to classical micrometer‐sized thermites. Here, we studied the combustion behavior of energetic composite composed of Al and chromium (III) oxide (Cr2O3) as function of the oxide particle size. Homogeneous composites were prepared by mixing Al nanoparticles (Φ≈50 nm) with Cr2O3 micro‐ and nanoparticles (Φ≈20 nm), respectively, in hexane solution. The dried Cr2O3/Al composite powders w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Different profiles can be divided into three and four zones for the Al/WO3 and the Al/WO3/PAni_LF composites, respectively. The combustion regimes are multistage, and based on our experience and knowledge [18,[32][33], an attempt to Finally, note that the combustion velocity of the PAni-doped nanothermites is of the same order of magnitude as that of the conventional binary Al/WO3 nanothermite. This result represents a truly major scientific breakthrough in the preparation of safer and more reliable reactive nanocomposites because the studies conducted for desensitising energetic nanocomposites and reported in the literature have always led to a drastic loss of reactivity [16,18].…”
Section: Combustion Performance Of Pani-doped Al/wo3 Nanothermitesmentioning
confidence: 99%
“…Different profiles can be divided into three and four zones for the Al/WO3 and the Al/WO3/PAni_LF composites, respectively. The combustion regimes are multistage, and based on our experience and knowledge [18,[32][33], an attempt to Finally, note that the combustion velocity of the PAni-doped nanothermites is of the same order of magnitude as that of the conventional binary Al/WO3 nanothermite. This result represents a truly major scientific breakthrough in the preparation of safer and more reliable reactive nanocomposites because the studies conducted for desensitising energetic nanocomposites and reported in the literature have always led to a drastic loss of reactivity [16,18].…”
Section: Combustion Performance Of Pani-doped Al/wo3 Nanothermitesmentioning
confidence: 99%
“…XRD patterns of CrO x were also measured on glass substrates to avoid signal overlapping with FTO. Although the ∼30 nm thick film shows weak signals, the ∼300 nm thick layer shows discrete peaks, most of which are attributed to Cr 2 O 3 (Figure c) . A weak signal at ∼31° is probably ascribed to CrO 3 , suggesting a coexistence of Cr 3+ and Cr 6+ .…”
Section: Resultsmentioning
confidence: 96%
“…Nanothermites and their derivatives can be also used as fast burning compositions for short pyrotechnics delays [109], with time bases ranging from milliseconds to microseconds per centimeter. The slowest fast delay systems could be prepared from gasless nanothermites such as Al/ Cr 2 O 3 [110,111], Al/NiO [112], or red P/Fe 2 O 3 [113]. The velocity can be adjusted by playing on the composition, the particle size of components and the density of mixtures.…”
Section: Applications and Integration In Systemsmentioning
confidence: 99%